Innovative Distance Learning Tool for Morphological Identification of Chigger Mites (Actinotrichida) as Vectors of Scrub Typhus: A Pilot Study - Kumlert, Rawadee (Trop Med Infect Dis, 2020)
Scrub typhus, a disease caused by Orientia tsutsugamushi, affects more than one billion people globally with an average fatality rate of 6%. Humans are accidentally infected through the bite of trombiculid mite larvae (chiggers). Chiggers feed on hosts’ extracellular fluid for survival and development. O. tsutsugamushi is maintained throughout the chigger’s lifespan and over several generations. Although disease-related knowledge is essential in designing effective control strategies, many personnel in related sectors are unfamiliar with this disease and its vector. To tackle this issue, we developed a distance learning tool using educational videos on scrub typhus- and vector-related topics. The learning method is facilitated online, and students and tutors are not required to be physically present at the same place and time, thus allowing flexibility and accessibility. Knowledge improvement of 34 participants from related sectors was evaluated by pre- and post-test questionnaires. Although 54% of participants had prior knowledge of scrub typhus, 76.5% still lack basic knowledge of vector identification. After the distance learning, the average score increased significantly from the baseline (p < 0.05). Most participants showed interest in the topic and learning method. These results suggest that the distance learning method was promising in distributing health-related information and might be applied to other diseases and communities.